Destination image : a study of Korean drama's influence on generation Y in Singapore - Tan, Sze Jie (2012)
This study aims to explore the impact of Korean dramas on perceptions of South Korea as a vacation destination. The study has three specific objectives. The first is to identify destination attributes important to local viewers. The second is to find out how Korean dramas impact viewers’ perception of South Korea. Lastly, the study explores how watching Korean drama impacts viewers’ motivations to travel to South Korea and the barriers for such a travel.